Sovereign bond spreads and CDS premia in the Eurozone: A causality analysis; Diferenciales de bonos soberanos y primas de CDS en la zona euro: Un análisis de causalidad - Cecilia Téllez; Margarita Martín García; María Ángeles Ramón Jerónimo; José Luis Martín Marín (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
This article presents an analysis of the possible relationship between the spreads of sovereign bonds and the premia of credit default swaps (CDS) to determine whether they are useful tools for the measurement of the sovereign risk either separately or by taking into account the joint evolution of their values. The data refer to ten countries in the Eurozone along 2008-2016. By applying the causality Granger test for these variables, after six different ways of proxy, CDS premia are found to be the cause of the risk spreads in certain cases, although a bidirectional relationship is predominant in many other cases. So the CDS market contains clear and highly useful information on the sovereign risk.
Keywords: G15; H63; 330; sovereign risk; credit risk; CDS; causality